ANALYSIS OF THE CAUSES OF NON LOANSAT THE MANAGEMENT BUMDES OF JATIMULYA VILLAGE WINOSARI DISTRICT BOALEMO DISTRICT - ngasemi iryana; Siske Anani; Syamsinah (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This study aims to determine the factors that cause bad credit in BUMDes Amanah, Jatimulya Village and to find out the management implementations carried out by BUMDes Amanah, Jatimulya Village. The method in this research is to use qualitative methods with the type of research that is descriptive. Qualitative research data obtained through interview techniques, participant observation, and documentation. In this study it was concluded that, (1) The factors causing bad credit in BUMDes Amanah DesaJatimulya were caused by the covid-19 pandemic, untrustworthy customers in using funds, less efficient performance of BUMDes officers and the occurrence of customer harvest failures (2) Management implementation What is done by BUMDes Amanah DesaJatimulya in dealing with bad loans is in an orderly way, namely directing debtors to apply for loans first, then verifying before being approved, signing a collective agreement. The loan limit provided by BUMDes Amanah is Rp. 5,000,000.00 with a period of six months.